Spatio-temporal estimations of ultraviolet erythemal radiation in Central Chile - Gonzalez-Rodriguez, Lisdelys; Rodriguez-Lopez, Lien; Jimenez, Jorge; Rosas, Jorge; Garcia, Wirmer; Duran-Llacer, Iongel; de Oliveira, Amauri Pereira; Barja Gonzalez, Boris (My University, 2022)
Solar ultraviolet radiation (UVR) plays an important role in environmental and occupational health. Although the importance of UVR and its spectral bands is well established, the characterization of spatio-temporal distributions has not been documented in Central Chile. This research estimated ultraviolet erythemal radiation (UVER) doses for the Mediterranean Region of Chile (MRCh) sites by using a simple model developed previously by us based on ground-based global solar irradiance. This provides monthly, seasonal, and annual basis maps of UVER exposure across MRCh. The model was validated using ground-based solar radiation measurements in three sites. The spatio-temporal distributions of UVER daily doses for MRCh on a monthly and annual were analyzed. The evolution of standard and minimal erythemal doses (SED/MED) for skin phototypes I-IV was calculated for the years 2015-2020. The UVER doses in the MRCh were greater than 2.6 kJm(-2) during most of the year and were relatively similar for the study area. The mean annual standard cumulative doses ranged from 14,149 to 10,146 SED, whereas the most common skin type in Chile (III-IV) receives an annual cumulative dose between 4,073 MEDIII and 3,161 MEDIV in the mountains (El Colorado) and between 2,926 MEDIII and 2,276 MEDIV in the coastal area (Valparaiso). The results can be used for public health awareness and to predict UVER levels at locations without measurement, providing useful information for decision-makers to offer insight into potential skin damage among the most populated area of Chile.
Keywords: uver; uver spatio-temporal distribution; annual cumulative doses; mediterranean region of chile